Basic Diving Training for Community Based Tourism (Pokdarwis) in Pandeglang District - Nuryadin, Arief; Rahayu, Ayu; Andria, Yogi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Pokdarwis is one of the spearheads of tourism which plays an important role in promoting tourist destinations and providing education related to these tourist destinations in the local area. The lack of knowledge and diving skills of Pokdarwis members, as well as the limited facilities and infrastructure that can be used to improve their diving skills is one of the reasons for the implementation of community service activities entitled Basic diving training for Community Based Tourism (Pokdarwis) in Pandeglang Regency. This activity uses the method of observation, interviews, training, and mentoring. This training activity was attended by 20 participants from the Pokdarwis of Pandeglang Regency. The results of this activity indicate that there are differences in the mean pretest and posttest scores, where the posttest score is greater than the pretest score. As many as 80% of the participants successfully carried out the SCUBA equipment installation procedure properly. 90% of participants were able to do the Giant Step Entry procedure well and 75% of the participants were able to do the Back Roll Entry procedure well. And finally, as many as 60% of the participants could do mask clearing well.